The six servants - Jacob; Grimm, Jacob; Grimm, Wilhelm; Bell, Anthea; Goloshapov, Sergei (New York : North-South Books, 1996)
Aided by six men with extraordinary abilities, a prince disguised as a commoner succeeds in outsmarting an evil enchantress and gaining her daughter's hand in marriage.
Keywords: Fairy tales; Folklore -- Germany